If the first four terms of the power series expansion of the solution of the differential equation satisfying the initial conditions is
. Then the value of is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
y ′ ′ ( x ) = ( 1 + x 2 ) y ( x )
Putting x = 0
y ′ ′ ( 0 ) = ( 1 + 0 ) y ( 0 ) = − 2
Differentiating the equation,
y ′ ′ ′ ( x ) = ( 1 + x 2 ) y ′ ( x ) + 2 x y ( x )
Put x = 0,
y ′ ′ ′ ( x ) = y ′ ( x ) = 2
The first four terms of the power series are,
y ( 0 ) + y ′ ( 0 ) x + 2 ! y ′ ′ ( 0 ) x 2 + 3 ! y ′ ′ ′ ( 0 ) x 3 = − 2 + 2 x − x 2 + 3 1 x 3
a + b + c + d = − 2 + 2 − 1 + 3 1 = − 3 2 ≈ − 0 . 6 6